AUDIT KOMUNIKASI PROGRAM PERTUNJUKAN SENI CAHAYA PADA MASA PANDEMI (STUDI KASUS : SUMONAR FESTIVAL 2020) - Ahimsa Adi Wibowo; Windri Saifuddin; Cindy Prastia Putri; Fira Nur Isnaini; Fina Salsabila Latif (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The Covid-19 pandemic has forced several art shows to be cancelled. However, under these circumstances, artists and art workers are looking for new opportunities to remain present in the public eye. One of them is by utilizing virtual exhibitions. This study aims to audit the communication process in a light arts performance program called SUMONAR FEST. This study uses a qualitative descriptive method with a case study approach and a communication audit. Data collection was carried out by studying literature through an online light art show event. The sample selection indicators are discussion events, performances, and SUMONAR FESTIVAL with the presentation of works that are representative and have an impact to inspire light art artists in the midst of the Covid-19 pandemic. The results showed that, SUMONAR FESTIVAL 2020 with the concept of Virtual Exhibition 360 succeeded in bringing the spirit of work for light art artists. The collaboration between the government, practitioners and the community is also a supporting factor for the sustainability of this activity in addition to utilizing technology in the form of Virtual Exhibition 360.